Reassessing the evidence of a survival advantage in Type 2 diabetes treated with metformin compared with controls without diabetes: a retrospective cohort study. (26th October 2022) - Keys, Matthew Thomas; Thinggaard, Mikael; Larsen, Lisbeth Aagaard; Pedersen, Dorthe Almind; Hallas, Jesper; Christensen, Kaare
Abstract: Background: Previous research has suggested that individuals with Type 2 diabetes and initiated on metformin monotherapy present with a survival advantage compared with the general population without diabetes. This finding has generated considerable interest in the prophylactic use of metformin against age-related morbidity. Methods: Utilizing Danish National Health Registers, we assessed differences in survival associated with metformin monotherapy for Type 2 diabetes compared with no diagnosis of diabetes in both singleton and discordant twin populations between 1996 and 2012. Data were analysed in both nested case–control and matched cohort study designs, with incidence rate ratios (IRRs) and hazard ratios estimated using conditional logistic regression and Cox proportional hazards regression, respectively. Results: In case–control pairs matched on birth year and sex or co-twin (sex, birth year and familial factors), incident Type 2 diabetes with treatment by metformin monotherapy initiation compared with no diagnosis of diabetes was associated with increased mortality in both singletons (IRR = 1.52, 95% CI: 1.37, 1.68) and discordant twin pairs (IRR = 1.90, 95% CI: 1.35, 2.67). After adjusting for co-morbidities and social indicators, these associations were attenuated to 1.32 (95% CI: 1.16, 1.50) and 1.64 (95% CI: 1.10, 2.46), respectively. Increased mortality was observed across all levels of cumulative use and invariant to a range of study designs and sensitivity analyses. Conclusions: Treatment initiation by metformin monotherapy in Type 2 diabetes was not associated with survival equal or superior to that of the general population without diabetes. Our contrasting findings compared with previous research are unlikely to be the result of differences in epidemiological or methodological parameters.